Assessment of acid-soluble collagen extracted from viscera of yellowfin tuna (Thunnus albacares) and milkfish (Chanos chanos) - Eleccion, Elizer; Bual, Ronald P.; Bantilan, Zesreal Cain; Pague, Job Jr.; Bacosa, Hernando P. (2025)
Despite its wide array of applications and unique properties, collagen – typically sourced from land animals – faces ethical, resource, and disease-related challenges. Fish viscera, often discarded as byproducts in the fishing industry, represent an untapped collagen reservoir. This study aimed to isolate and characterize acid-soluble collagen (ASC) from the viscera of yellowfin tuna and milkfish. The process involved deproteinization, defatting, filtration, precipitation, purification, and extraction using 0.5M acetic acid. The extracted ASC underwent physical and chemical analyses. Collagen yields from milkfish and yellowfin tuna were 8.35 ± 0.14% and 4.99 ± 0.05%, respectively. Differential scanning calorimetry revealed melting temperatures of 101.80 °C and 105.89 °C for milkfish and yellowfin tuna, respectively. Glycine predominated in the amino acid composition of yellowfin tuna, while proline prevailed in milkfish. Fourier transform infrared analysis showed a triple helical structure with a band intensity ratio of approximately 1.0 between the Amide III and 2450 cm–1. Visual examination of ASC resembled a soft sponge conformation. Scanning electron microscopy revealed ASC’s porous, interconnected, and fibrillar structure. This study demonstrates that collagen can be effectively extracted from the viscera of yellowfin tuna and milkfish, showcasing promising physicochemical characteristics for various potential applications.
Keywords: Milkfish; Yellowfin tuna